Cost Analysis Due to the Addition of Working Time on Periodic Road Maintenance Project on Jl. Ir. Soekarno Ruas 3 Blitar City - Eka Shodiq Permadi; Hanie Teki Tjendani; Budi Witjaksana (International Journal of Industrial Innovation and Mechanical Engineering, 2025)
Prolonged road damage disrupts community mobility, logistics activities, and reduces road user safety. The road maintenance project on Jl. Ir. Soekarno in Blitar City, which was planned to be completed in 120 days with a budget of Rp1.16 billion, experienced a delay of 8 days due to time management constraints. This study aims to evaluate the use of the Time Cost Trade Off (TCTO) method to accelerate project completion without reducing the quality of work. The TCTO method is used to analyze the relationship between time and cost. This research proposes additional overtime working hours of 2 hours per day with the assumption of resources according to the Cost Budget Plan (RAB). The results show that with this method, the project can be completed in 117 days at a total cost of Rp1,342,177,724. Although it requires additional costs, this acceleration allows the project to be completed faster than the previous condition